2014
DOI: 10.1590/1415-52732014000200007
|View full text |Cite
|
Sign up to set email alerts
|

School Gardens in the Distrito Federal, Brazil

Abstract: OBJECTIVE: The aim of the present study was to identify experiences with gardens in public schools in the Distrito Federal, Brazil, and to analyze factors involved in their use to promote healthy eating habits. METHODS: This is an analytical cross-sectional study with data collection in two phases: (1) telephone contact with all public schools in the Distrito Federal; (2) interviews conducted with a sample of schools with a garden (n=105). RESULTS: Of the 582 schools in the Distrito Federal, 453 (77.8%) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 18 publications
0
11
0
12
Order By: Relevance
“…Esta questão poderia indicar que, ainda que muitas vezes realizem a função "na prática", eles não se sintam, de fato, como os maiores responsáveis pelo espaço ou tenham menor valorização do seu trabalho. Similarmente, em estudo realizado no Distrito Federal, 29 foi descrito que os professores eram os mais envolvidos com o cuidado e manutenção das hortas escolares.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Esta questão poderia indicar que, ainda que muitas vezes realizem a função "na prática", eles não se sintam, de fato, como os maiores responsáveis pelo espaço ou tenham menor valorização do seu trabalho. Similarmente, em estudo realizado no Distrito Federal, 29 foi descrito que os professores eram os mais envolvidos com o cuidado e manutenção das hortas escolares.…”
Section: Discussionunclassified
“…Bernardon et al 29 observaram que, na sua população, 31% das escolas tiveram suas hortas desativadas em algum estágio, listando como principais desafios a falta de recursos, de mão de obra e a falta de tempo dos professores para tratar do tema dentro do currículo. Outros autores também relataram a falta de recursos, de envolvimento dos professores, de tempo, e a manutenção como desafios para as hortas pedagógicas.…”
Section: Discussionunclassified
“…Bernardon et al 15 found that the use of gardens as an instrument for promoting healthy eating habits was most evident when the objective of the project was to complement the meals served within the school, thereby becoming part of the children´s daily diet. Similarly, Wansink et al 30 found that a statistically higher proportion of children chose vegetables from the school buffet when these had been grown in the school garden.…”
Section: Discussionmentioning
confidence: 99%
“…15 The majority of studies published to date report results of interventions involving school gardens as short-term programs. 12,16,17 However, there is a scarcity of studies in the literature reporting experiences of school gardens that are integrated into the school curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The use of school gardens in Brazil is not new, yet scarce studies addressing the use of this type of strategy with students are available. 16 Two public power initiatives promoting the development of school gardens in Brazil are worth of mention: the Health at School Program (Programa Saúde na Escola), which promotes pedagogical school gardens as a strategy for knowledge building and skills development among school children, enabling them to produce, discover, select and consume foods in an adequate, healthy, safe and playful manner; 19 and the joint initiative of the Food and Agriculture Organization (FAO) with the Brazilian Education Development Fund (FNDE), called "Educating with School Gardens (Educando com a Horta Escolar), which provides educational activities in food and nutrition within schools through school-based gardens and practical classes in a range of different subjects involving both teachers and students, and fosters an integrated discussion on food, nutrition, the environment and school curriculum. 20 Some studies have reported experiences and topics within schools involving the gardens implemented under the program, including agroecology, 21 science teaching, 22 sustainable practices; 23 environment education, 24 among others.…”
Section: 14mentioning
confidence: 99%